Imaginaries in Contemporary Aesthetics (Imaginations: Journal of Cross-Cultural Image Studies, 2017)
Abstract | What is the relationship between visual images and the social imaginary? The following article argues that the social imaginary is built on aesthetics and that this fact creates conditions of perception belonging not to art but to the social realm. It also means that it is possible, therefore, to construct a triadic model of social perception, according to whether an empirical fact or an imagined event dominates in any given phenomenon. How then is visual perception created through the production of the imaginary? If an imaginary is a state of aesthetic cognition then there is an epistemic relationship of continuity between the visual image and the construction of the social imaginary which precedes all representation.Résumé | Quelle est la relation entre les images visuelles et l’imaginaire social? Cet article soutient que l’imaginaire social repose sur l’esthétique et que cela crée des conditions de perception appartenant non pas à l’art, mais à la sphère sociale. Cela signifie aussi qu’il est possible de construire un modèle tripartite de la perception sociale selon qu’un fait empirique ou un événement imaginé domine dans un phénomène donné. Comment la perception visuelle est-elle donc créée en fonction de la production de l’imaginaire social? Si l’imaginaire est un état de connaissance esthétique, il existe une relation épistémique de continuité entre l’image visuelle et la construction de l’imaginaire social qui précède la représentation.